Answer:
4/10
Step-by-step explanation:
Option A
If f(x) =
and g(x) =
then ![(f - g)(x) = x^2 + 8](https://tex.z-dn.net/?f=%28f%20-%20g%29%28x%29%20%3D%20x%5E2%20%2B%208)
<em><u>Solution:</u></em>
Given that f(x) =
and g(x) = ![x^2 - 7](https://tex.z-dn.net/?f=x%5E2%20-%207)
To find: (f - g)(x)
We know that,
(f – g)(x) = f (x) - g(x)
Let us substitute the given values of f(x) and g(x) in above formula,
![(f - g)(x) = 2x^2 + 1 - (x^2 - 7)](https://tex.z-dn.net/?f=%28f%20-%20g%29%28x%29%20%3D%202x%5E2%20%2B%201%20-%20%28x%5E2%20-%207%29)
For solving the brackets in above expression,
There are two simple rules to remember:
When you multiply a negative number by a positive number then the product is always negative.
When you multiply two negative numbers or two positive numbers then the product is always positive.
So the expression becomes,
![(f - g)(x) = 2x^2 + 1 -x^2 + 7](https://tex.z-dn.net/?f=%28f%20-%20g%29%28x%29%20%3D%202x%5E2%20%2B%201%20-x%5E2%20%2B%207)
Combining the like terms,
![(f - g)(x) = 2x^2 - x^2 + 1 + 7\\\\(f - g)(x) = x^2 + 8](https://tex.z-dn.net/?f=%28f%20-%20g%29%28x%29%20%3D%202x%5E2%20-%20x%5E2%20%2B%201%20%2B%207%5C%5C%5C%5C%28f%20-%20g%29%28x%29%20%3D%20x%5E2%20%2B%208)
Thus option A is correct
Answer:
r is a straight line
completing or enhancing something.
Step-by-step explanation:
1/9
Find the common denominator, 1/3 can be multiplied to get to ninths. 1/3 is equivalent to 3/9, and so 4/9 minus 3/9 is 1/9.